Pengaruh Pengembangan Karir terhadap Retensi Karyawan dengan Kepuasan Kerja sebagai Intervening Dinas PUPR Provinsi Jambi - Dila Aprillia Hendriyulianti (Master Manajemen, 2025)
This study aims to test whether career development will affect employee retention through job satisfaction as an intervening variable at the Public Works and Public Housing Agency of Jambi Province. This study took samples from several civil servants of the Public Works and Public Housing Agency of Jambi Province totaling 70 people. Data collection was carried out using questionnaires that were distributed directly. This study used quantitative analysis carried out using the SmartPLS 4.1.1 application. The results of this study indicate that: 1) career development has a positive and significant effect on employee retention, 2) career development has a positive and significant effect on job satisfaction, 3) job satisfaction has a positive and significant effect on employee retention and 4) career development has a positive and significant effect on employee retention through job satisfaction.